2022
DOI: 10.1111/ffe.13858
|View full text |Cite
|
Sign up to set email alerts
|

Data‐driven prediction of the probability of creep–fatigue crack initiation in 316H stainless steel

Abstract: Stainless steel components in advanced gas‐cooled reactors (AGRs) are susceptible to creep–fatigue cracking at high temperatures. Quantifying the probability of creep–fatigue crack initiation requires probabilistic numerical simulations; these are complex and computationally intensive. Here, we present a data‐driven approach to develop fast probabilistic surrogate models of creep–fatigue crack initiation in 316H stainless steel. We perform a set of Monte Carlo simulations based on the R5V2/3 high temperature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Many supervised learning algorithms have been applied to crack initiation prediction, fatigue life prediction, and other engineering fields. Chavoshi and Tagarielli 115 propose a data‐driven approach to determine probabilistic surrogate models of stainless steel components creep–fatigue crack initiation in advanced gas‐cooled reactors at high temperatures. Numerous supervised learning algorithms have been employed, and it has been observed that the gradient tree boosting algorithm yields the highest accuracy.…”
Section: Ml‐based Methods For Fatigue Life Prediction Of Am Metalsmentioning
confidence: 99%
“…Many supervised learning algorithms have been applied to crack initiation prediction, fatigue life prediction, and other engineering fields. Chavoshi and Tagarielli 115 propose a data‐driven approach to determine probabilistic surrogate models of stainless steel components creep–fatigue crack initiation in advanced gas‐cooled reactors at high temperatures. Numerous supervised learning algorithms have been employed, and it has been observed that the gradient tree boosting algorithm yields the highest accuracy.…”
Section: Ml‐based Methods For Fatigue Life Prediction Of Am Metalsmentioning
confidence: 99%
“…[19][20][21] Moreover, the critical location of creepfatigue failure will shift from the surface to the subsurface as the fraction of creep damage increases in the creep-fatigue interactions. [22][23][24][25][26] Therefore, a full-time description of stress/strain response and evaluation of damage accumulation is necessary for the blades under actual loading conditions, which can be performed by the combination of constitutive modeling and damage evaluation method. A unified viscoplasticity constitutive model (UVCM) for describing the deformation behavior has been widely used in the field of materials science and engineering.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to obtain the real‐time stress/strain distribution and damage accumulation of the blades under actual loading conditions 19–21 . Moreover, the critical location of creep–fatigue failure will shift from the surface to the subsurface as the fraction of creep damage increases in the creep–fatigue interactions 22–26 . Therefore, a full‐time description of stress/strain response and evaluation of damage accumulation is necessary for the blades under actual loading conditions, which can be performed by the combination of constitutive modeling and damage evaluation method.…”
Section: Introductionmentioning
confidence: 99%
“…surface roughness, manufacturing tolerances, heat treatment and cutting-tool wear) is of great importance to structural integrity assessments of turbine bladed disks. Generally, deterministic approaches together with safety factor accounting for uncertainties often cause conservative results (Schijve, 2005;Niu et al, 2021a, b), while probabilistic structural integrity assessments (Narayanan, 2020;Chavoshi and Tagarielli, 2023) permit the uncertainties to be reflected in the quantification of reliability in fatigue design. It's worth mentioning that finite element analysis (FEA) together with probabilistic methods provides an efficient solution to evaluate the fatigue performance and reliability of turbine bladed disks under multisource uncertainties.…”
Section: Introductionmentioning
confidence: 99%